POSIADŁOŚCI KAMERALNE MISTRZÓW BALIWATU BRANDENBURSKIEGO JOANNITÓW NA OBSZARZE DIECEZJI LUBUSKIEJ DO KOŃCA XV WIEKU – ZARYS PROBLEMATYKI - Wasilkiewicz, Kamil (In Gremium. Studies in History, Culture and Politics, 2016)
The demesn es of masters of the Bailiwick of Brandenburg on the territory of the Diocese of Lebus until the end of 15th century – problematic framework The Knights Hospitaller appeared on the territory of the Bishopric of Lebus in the first part of 15th century. They took possession of former dominions of the Templars, which was a consequence of decision made by the pope Clement V (the bull Ad providam of 2 May 1312) and the Treaty of Kremmen, that was concluded between the Hospitallers and Waldemar the Great, the Margrave of Brandenburg (29 January 1318). Commandries of the brothers of Saint John, which were located in the Diocese of Lebus, were part of the Bailiwick of Brandenburg. The head of the administrative unit was called a master, who was named Herrenmeister (sometimes also a bailiff ora preceptor). Demesnes were one of the mainstay of the high social status of masters of the Bailiwick of Brandenburg. They were complexes of landed which provided funds and material assets for bailiffs. The main aim of this article was to show the functioning of demesnes of masters the Bailiwick of Brandenburg in area of the Bishopric of Lebus to the end of 15th century.